SUSTAINABLE STRATEGIES MANAGEMENT OF AESTHETIC LEARNING IN GUANGXI ETHNIC MUSEUM - Linlin, Wang Linlin; Chueysai, Somdej (Asia Pacific Journal of Religions and Cultures, 2025)
Sustainable strategies for managing aesthetic learning in Guangxi Ethnic Museum are deeply intertwined with the region's cultural beliefs and religious practices, as they emphasize the preservation and promotion of traditional art forms rooted in local spiritual and cultural identity. By integrating these cultural and religious elements into educational programs, the museum fosters a holistic understanding of the community's heritage, ensuring its continuity through adaptive and responsible stewardship. This article examines sustainable strategies for managing aesthetic learning in the Guangxi Ethnic Museum through the lens of the region's cultural beliefs and religious practices. It delves into how these traditions shape and influence the museum's educational initiatives, ensuring the preservation and transmission of indigenous art forms. By integrating spiritual and cultural values into the museum’s aesthetic learning frameworks, the study underscores the significance of culturally responsive management that adapts to the evolving needs of both the community and broader society. This approach highlights the essential role of sustainability in safeguarding the aesthetic and cultural heritage of Guangxi’s ethnic communities for future generations. This article presented (1) sustainable strategies management of aesthetic learning in Guangxi ethnic museum, and (2) recommendation for aesthetic education management of Guangxi Ethnic Museum.